The Leaching of Cobalt in Platinum-Cobalt Fuel Cell Catalysts - Ranganthan, Omishka (Department of Chemical Engineering, 2023)
Platinum-cobalt catalysts have proved to be promising alternatives to the conventional platinum catalyst used for the ORR reaction at the cathode of PEM fuel cells. These catalysts, however, undergo leaching of cobalt in the harsh environment of the fuel cell during its operation as well as during catalyst ink preparation and conditioning. Several methods have been developed and are currently being used to characterise this leaching, however, these methods are long and complicated or only quantify cobalt loss before and after operation and not during the process. In this study a unique method of testing cobalt leaching was developed, which involves utilizing the magnetic properties of the alloy through the use of an in-situ magnetometer. This method is able to characterise the cobalt mass during catalyst ink preparation as well as during fuel cell operation. Furthermore, it may allow for uninterrupted catalyst characterisation during fuel cell operation. The leaching occurring during electrode preparation was tested using this methodology in this study. The method involved removing the reactor typically placed in the magnetometer with a titanium sample holder providing minimal background signal. The detection limits of the magnetometer were investigated, and it was found that the minimum amount of cobalt loaded on an individual electrode was 0.5 mg. It was also determined that the electrode surface area should not exceed 6.25 cm2 in order to obtain a high magnetic signal. The electrodes were taped to the sample holder which was clamped to the arm of the oscillating arm of the magnetometer and aligned. Data of magnetisation as a function of magnetic field strength were used for calibration as well as electrode leaching tests. The calibration curve was constructed by varying amounts of catalyst loaded on individual electrodes and determining the magnetic signals for each. Electrode leaching tests involved catalyst and ionomer forming an ink which was coated on electrodes with different loadings. The magnetic responses were obtained for each electrode. In addition, tests involving a similar methodology with the catalyst or catalyst ink were conducted, which allowed accurate time on stream data of the leaching process. Three different catalysts – PtCo/C, PtCo2/C and Pt3Co/C were synthesised using an organometallic chemical deposition synthesis method and characterised XRD and SEM-EDS analyses. Different masses of these catalysts were dusted on individual Toray paper gas diffusion electrodes and the saturation magnetisation for each loading of all catalysts was used to construct calibration curves. Superparamagnetic behaviour was observed, therefore sizing of the crystallites was possible. Three catalyst inks were made for each alloy catalyst consisting of Nafion solution, water and isopropanol. These were brush coated on electrodes that were tested in the magnetometer. These results showed that the PtCo2/C catalyst experienced a high degree of leaching during electrode preparation, which increased with an increase in initial cobalt loaded. The leaching, or cobalt loss was between 28% - 50%. The Pt3Co/C catalyst experienced the least amount of leaching with a maximum of 13%. The PtCo/C catalyst experienced 26 – 55%, which was similar to the PtCo2/C catalyst. Leaching was analysed with time and temperature, and it was found that an increase in temperature increased the rate of leaching. Leaching occurred immediately when the Nafion ionomer was in contact with the catalyst. Miniature fuel cells were designed to implement this methodology in order to test leaching occurring during the other stages of the fuel cell – conditioning and operation. These cells are designed to contain minimal ferromagnetic material to minimise background signal.